Development of History Textbooks using Model MORE (Model, Observe, Reflect, Explain) - Sutoyo Budiharto; Nasution Nasution; Ismet Basuki (The Indonesian Journal of Social Studies, 2019)
Development research aims to produce effective historical textbooks for use in historical learning. Historical textbooks developed using the learning model MORE (model, observe, reflect, explain). The type of research is development by adapting the Thiagarajan 4-D development model. Data collection techniques in this study used a sheet of validation, questionnaire, observation, and test. Data obtained from the results of the study were analyzed by statistical and descriptive tests. The empirical test in this study used themethod pre-experimental withdesign one group pretest posttest. The subjects of this study were students of class X IPS 2 at MAN 1 Pontianak. Research results, 1) The quality of the history textbook model MORE has good quality based on the evaluation of the validator. 2) Historical textbooks using themodel MORE can have a significant influence on historical learning.